Energy Prices, Energy Poverty, and Well-Being: Evidence for European Countries - Heinz Welsch; Philipp Biermann (University of Oldenburg, Department of Economics, 2014)
This paper uses data on the life satisfaction of more than 100,000 individuals in 21 European countries, 2002-2011, to study the relationship between subjective well-being and the prices for households of electricity, oil and gas. We find that energy prices have statistically and economically significant effects on subjective well-being. The effect sizes are smaller than but comparable to the effects of important personal factors of well-being. Effects above average are found in individuals from the lowest income quartile. In addition, effects are strongest at times when required energy expenditures can be expected to be high. The empirical results are consistent with the prediction that greater energy poverty implies a greater effect of energy prices on well-being.
Keywords: Q41; I31; D12; 330; energy price; energy poverty; fuel poverty; consumer welfare; subjective well-being